Calibration of NOMAD on ExoMars Trace Gas Orbiter: Part 3 - LNO validation and instrument stability. (1st September 2022) - Cruz Mermy, G.; Schmidt, F.; Thomas, I.R.; Daerden, F.; Ristic, B.; Patel, M.R.; Lopez-Moreno, J.-J.; Bellucci, G.; Vandaele, A.C.; ,
Abstract: The LNO channel is one of the 3 instruments of the NOMAD suite of spectrometers onboard the ExoMars Trace Gas Orbiter currently orbiting Mars. Designed to operate primarily at nadir at very high spectral resolution in the 2.3 ​ μ m–3.8 ​ μ m spectral region, the instrument observes the martian atmosphere and surface daily since March 2018. To perform an accurate calibration of the instrument, in-flight measurement needs to be integrated to account for potential change during the cruise phase and later during the mission. In a companion article, Thomas et al. this issue, PSS, 2021 proposed a method based on the use of 6 observation sequences of the sun by LNO to derive a self-consistent approach, assuming temporal stability. Here we report an alternative concept of calibration, model the instrument using basic principle, based on the comparison between each solar spectrum observed and a reference solar spectrum. The method has the advantages to allows testing of the temporal stability but also instrumental effects such as temperature. It encompasses the main transfer functions of the instrument related to the grating and the AOTF and the instrument line shape using 9 free parameters which, once inverted, allow the observations to be fitted with an acceptable Root Mean Square Error (RMSE) around 0.5%. We propose to perform a continuum removal step to reduce the spurious instrumental effect, allowing to directly analyze the atmospheric lines. This methodology allows quantifying the instrumental sensitivity and its dependence on temperature and time. Once the temperature dependence was estimated and corrected, we found no sign of aging of the detector. Finally, the parameters are used to propose an efficient calibration procedure to convert the LNO-NOMAD data from ADU to radiances with spectral calibration and the instrument line shape. A comparison with the method reported in Thomas et al. this issue, PSS, 2021 showed that both calibrations are in agreement mostly within 3%. Highlights: The LNO channel is 1 of 3 spectrometers in NOMAD on ExoMars Trace Gas Orbiter. The LNO channel observes Mars in limb, nadir and solar occultation modes. This article describes an alternative method of calibration for the LNO channel data. The method is ​based on a comparison between observation of the sun by the LNO channel and a synthetic solar spectrum. Temperature and time dependence of the instrumental responsivity were tested. Nadir observations can be calibrated radiometrically.